House prices wealth effect and labor supply - Richard Disney; John Gathergood (Institute for Fiscal Studies (IFS), 2014)
We examine the impact of housing wealth on labor supply decisions using data on exogenous local variation in house prices merged into household panel data for Britain. Our estimates are conditioned on variations in local labor demand and income expectations as these may co-determine housing wealth and labor supply. We use renters as a control group and test for the potential endogeneity of tenure and location. We find significant housing wealth effects on labor supply among young married / co-habiting female owners and older male owners, consistent with leisure being a normal good. The size of these effects is economically important. Our estimates imply housing wealth effects have stronger effects then local labor market conditions upon participation decisions for these workers.
Keywords: E21; J22; 330; Labor supply; Wealth effects; House prices